2016
DOI: 10.13189/ujer.2016.040532
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Life Style Behaviors of University Students of School of Physical Education and Sports in Terms of Body Mass Index and Other Variables

Abstract: The aim of this study is to determine Healthy Lifestyle Behaviors of students in the Schools of Physical Education and Sport (SPES) utilizing Body Mass Index (BMI) and other various variables. The study is composed of 1695 students studying in SPES, in 14 different universities across Turkey. It is made up of 1067 male and 624 female students. Data collected, is from both anonymous personal information and a Healthy Lifestyle Behaviors Scale-I survey. SPSS 21 was used and analysis obtained is 95% reliant. Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The findings of the current study revealed that the HPLP-II total score of the athlete university students was moderate (130.41 ± 22.93), the highest healthy lifestyle behaviors were spiritual growth and interpersonal relationships, and the lowest behaviors were health responsibility and nutrition. Previous studies in the literature show that Turkish athlete university students had moderate HPLP-II scores, that the highest scores were spiritual growth/self-actualization, interpersonal relationships, and the lowest scores were physical activity, stress management, and nutrition (55,56). In addition, this study also revealed a lowlevel negative correlation between HPLP-II total, physical activity, spiritual growth, interpersonal relationships, stress management scores, and depression scores of the participants.…”
Section: Discussionsupporting
confidence: 64%
“…The findings of the current study revealed that the HPLP-II total score of the athlete university students was moderate (130.41 ± 22.93), the highest healthy lifestyle behaviors were spiritual growth and interpersonal relationships, and the lowest behaviors were health responsibility and nutrition. Previous studies in the literature show that Turkish athlete university students had moderate HPLP-II scores, that the highest scores were spiritual growth/self-actualization, interpersonal relationships, and the lowest scores were physical activity, stress management, and nutrition (55,56). In addition, this study also revealed a lowlevel negative correlation between HPLP-II total, physical activity, spiritual growth, interpersonal relationships, stress management scores, and depression scores of the participants.…”
Section: Discussionsupporting
confidence: 64%
“… 24 Besides, the questionnaire was tested for validity and reliability in previous studies and was found valid and reliable. 2 , 25 The reliability coefficient (Cronbach's α) for this study was 0.83, this indicates that the instrument has acceptable internal consistency. The higher score indicates higher health literacy skills and vice-versa.…”
Section: Methodsmentioning
confidence: 55%
“…Healthy lifestyle behaviors are considered important means to reduce the burden of diseases as well as bring the person's general health to the highest level of well-being and self-efficacy. 1 3 University life is a critical period among students since they take on new responsibilities and decision-making roles when they arise away from their homes and families. 4 Many studies proved that healthy lifestyle behaviors had a significant impact on undergraduate student's life, and they are prone to share risky behaviors resulting in a significant impairment in health status.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy lifestyle behavior is also defined as all behaviors that are believed and applied by individuals to be healthy, maintain health and avoid disease (Çelebi et al, 2017). Healthy lifestyle behavior aims not only to prevent an illness or disease but also to bring a person's general health to better level (Bozlar dan Arslanoğlu, 2016).…”
Section: Introductionmentioning
confidence: 99%